Melek Literasi Basis Budaya Sekolah di SD Berdasarkan Hasil Analisis Artikel - Jannah Mutiarani Pradana; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
This article aims to examine the influence of school cultural base literacy in elementary schools in various different applications, so the author needs to examine several articles to find out the application of literacy in these schools. The research method used in this article is a qualitative approach with a literature study method. The method for reviewing journals was used by searching and collecting literature studies with the keyword